Effects on early mathematics of a program using games, picture books and worksheets - Connie Shin @ Connie Cassy Ompok; Musirin bin Mosin; Jusiah Idang; Noraina binti Noraidi (Conscientia Beam, 2025)
This study examines the effect of three teaching methods, i.e., games, picture books, and worksheets on early mathematics performance among preschool children. The research utilized the test of early mathematics abilities aligned with Malaysia's National Standard Preschool Curriculum. A quantitative approach was adopted employing a multi-site quasi-experimental design with 1,100 preschool children aged 4 and 5 from national preschools in Sabah, Malaysia. Data analysis was conducted using one-way ANOVA and ANCOVA through SPSS version 28. Among the three methods tested (play-based, picture books, and worksheets), the play-based method yielded the highest achievement followed by worksheets and picture books. Although the intervention program implemented in this study did not produce dramatic improvements, it provides positive insights into preschool children's potential for early mathematics performance, especially the importance of using this method in large groups to optimize children’s knowledge acquisition and skills. The results revealed a significant impact of teaching methods on early mathematics performance. Teachers should utilize play-based teaching methods to the greatest extent possible to enhance the early math achievement of preschool children.